Pro Multithreading and Memory Management for iOS and OS X - Sakamoto, Kazuki; Furumoto, Tomohiko; SpringerLink (Online service) (Berkeley, CA : Apress, 2012)
If you want to develop efficient, smooth-running applications, controlling concurrency and memory are vital. Automatic Reference Counting is Apple's game-changing memory management system, new to Xcode 4.2. Pro Multithreading and Memory Management for iOS and OS X shows you how ARC works and how best to incorporate it into your applications. Grand Central Dispatch (GCD) and blocks are key to developing great apps, allowing you to control threads for maximum performance. If for you, multithreading is an unsolved mystery and ARC is unexplored territory, then this is the book you'll need to make these concepts clear and send you on your way to becoming a master iOS and OS X developer. What are blocks? How are they used with GCD? Multithreading with GCD Managing objects with ARC
Keywords: Computer science; Computer Science; Computer Science, general